Effects of 8-week high-intensity interval training and moderate-intensity continuous training on bone metabolism in sedentary young females - Mingyue Lu; Mingxing Li; Longyan Yi; Feifei Li; Lin Feng; Tianyi Ji; Yanpeng Zang; Junqiang Qiu (Elsevier, 2022)
Background/Objectives: High-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) have been reported as effective exercise modes on bone metabolism. However, very few studies focused on young women with sedentary behavior. The purpose of this study was to investigate the effects of 8-week HIIT on bone metabolism in sedentary young women. Methods: 26 healthy, sedentary female participants were randomly assigned to either the HIIT (n = 13, age 23.2 ± 2.9 yr, weight 59.2 ± 7.2 kg, height 162.9 ± 3.3 cm, body mass index 22.3 ± 2.7 kg/m2) or MICT (n = 13, age 21.9 ± 1.7 yr, weight 59.3 ± 6.6 kg, height 160.9 ± 4.4 cm, body mass index 21.6 ± 2.4 kg/m2) group. Both groups completed 8 weeks (3 sessions/week) of training on the treadmill, where the HIIT group were asked to complete 6 × 3-min bouts of running at the intensity of 80-90% maximum oxygen uptake (VO2max) separated by 2-min active recovery at 30-40% VO2max and the MICT group completed 30-min continuous running at the intensity of 60-70% VO2max. The body composition, bone mineral density (BMD), calcaneus quantitative ultrasound, bone turnover markers, and lower limb muscle strength were measured pre and post interventions. Results: After 8-week interventions, 1) The total body BMD (HIIT, +8.5%; MICT, +5.5%) significantly increased (p < 0.05) without difference between the two groups (p > 0.05). The calcaneus broadband ultrasound attenuation (CBUA) (HIIT, +16.0%; MICT, +4.6%) and calcaneus stiffness index (CSI) (HIIT, +16.7%; MICT, +2.5%) significantly increased in HIIT group (p < 0.05), but not in MICT group (p > 0.05). 2) The 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) (HIIT, +42.8%; MICT, +24.9%) level increased in both groups with significantly higher changes in HIIT (p < 0.05). 3) The score of standing long jump (HIIT, +10.3%; MICT, +3.8%) and vertical jump (HIIT, +5.3%; MICT, +2.0%) increased in both groups with significantly higher changes in HIIT (p < 0.05). Conclusions: It suggested that 8-week HIIT and MICT interventions could improve bone metabolism. Compared with a similar workload of MICT, HIIT elicited superior benefits on bone metabolism.